Dossier génétique de « submersion de la peine » de Mohammed Dib (Formulaires, Le Seuil, 1970) - Karolina Resztak (Continents manuscrits)
This paper proposes a possible genesis of “submersion de la peine”, poem from the collection Formulaires by Mohammed Dib. The contingencies of dossier génétique fit closely to these ones of the poem’s mood evolution leading from lyricism to metaphysics and appearance to comprehend meantime a pictorial inspiration by Claude Lorrain’s works.